ANALYSIS OF FINANCIAL SERVICES AUTHORITY EMPLOYEES' COMPETENCE IN THE REGULATION AND SUPERVISION OF FINANCIAL INSTITUTIONS - Ateng Kusnandar Adisaputra (JEMBA: Journal of Economics, Management, Business and Accounting, 2023)
The Financial Services Authority or Otoritas Jasa Keuangan (OJK) was formed with the aim that all activities in the financial services sector: are organized regularly, fairly, transparently and accountably, are able to realize a financial system that grows in a sustainable and stable manner, and is able to protect the interests of consumers and the public. The duties, functions, and authorities of the OJK are very heavy and complex because they are related to regulation and supervision in the field of financial services. The implementation of OJK's duties, functions, and authorities in regulating and supervising the financial services sector needs to be supported by the availability of OJK employees who have competence in accordance with developments in the financial services sector. The competence of OJK employees must include a combination of skills, knowledge, and attitudes, namely: Technical Competence or technical competence, Managerial Competence or managerial competence, Interpersonal Competence or Social/Communication Competence. The method in this writing uses a literature study, by examining: books, scientific journals, laws and regulations, online materials, and other sources.